Evaluasi Tata Kelola Angkutan Pembuangan Sampah Tempat Pembuangan Akhir (TPA) dalam Mewujudkan Kota Tanjungpinang Ramah Lingkungan - Pranedya Derina Visanty; Alfiandri Alfiandri; Jamhur Poti (Universitas 17 Agustus 1945, 2026)
This study is based on the suboptimal management of waste transportation in Tanjungpinang City, caused by limited fleet capacity, uneven service routes, a lack of human resources, and inconsistent implementation of Standard Operating Procedures (SOPs). This situation has led to waste accumulation at various points and an excessive load on the Ganet Final Disposal Site (TPA), which uses a controlled landfill system. The system aims to minimize pollution through waste compaction, soil covering, and leachate and methane gas management, but its implementation has not been optimal due to limited facilities and infrastructure. This study aims to evaluate the management of waste transportation to the Ganet landfill and identify the obstacles that arise. The approach used is descriptive qualitative with observation techniques, in-depth interviews, and document analysis, involving the Environmental Agency, the Ganet Landfill Technical Implementation Unit, field officers, fleet drivers, and residents around the Temporary Cleaning Site (TPS). The findings reveal that waste transportation management is already being carried out through standard operating procedures (SOPs) and inter-unit coordination, but is still hampered by fleet limitations, landfill capacity that is nearly full, service routes that do not cover the entire area, and minimal community participation. Therefore, additional fleets, infrastructure improvements, strengthened supervision, and community outreach are needed to achieve sustainable waste management.